Strategi migran Banjar - Arbain, Taufik, 1974- (Yogyakarta : Penerbit dan distribusi, LKiS Yogyakarta, 2009)
Adaptation strategy of Banjarese people with the local people in Palangkaraya.
Includes bibliographical references (p. 251-256) and index.
Keywords: Banjar (Indonesian people) -- Cultural assimilation -- Indonesia -- Palangka Raya; Palangka Raya (Indonesia) -- Ethnic relations; Palangka Raya (Indonesia) -- Population